2003
DOI: 10.1046/j.1365-2826.2003.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Gonadotropin‐Releasing Hormone II Is Not a Physiological Regulator of Gonadotropin Secretion in Mammals

Abstract: Gonadotropin-releasing hormone (GnRH)-II stimulates luteinizing hormone (LH) and follicle-stimulating hormone (FSH) secretion when administered at high doses in mammals, and this effect has been assumed to be mediated through the GnRH-II receptor expressed on gonadotropes. This study used two selective GnRH-I receptor antagonists to test the alternative hypothesis that GnRH-II acts through the GnRH-I receptor to elicit gonadotropin secretion. The antagonist, antide, was used to characterize the receptor-relay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 47 publications
(66 reference statements)
1
26
0
1
Order By: Relevance
“…This conjecture has been supported recently by studies in shrews, sheep and primates. Although Type-2 GnRH receptors are reportedly present in mammalian gonadotropes, GnRH II stimulation of pituitary gonadotropins is completely blocked with administration of Type-1 GnRH receptor antagonists, both in vitro and in vivo [65][66][67]. Likewise, similar blocking effects of Type-1 receptor antagonists were found on GnRH II-induced ovulation in female musk shrews (TABLE 2) [68].…”
Section: Role Of Mammalian Gnrh II In Gonadotropin Releasementioning
confidence: 68%
See 2 more Smart Citations
“…This conjecture has been supported recently by studies in shrews, sheep and primates. Although Type-2 GnRH receptors are reportedly present in mammalian gonadotropes, GnRH II stimulation of pituitary gonadotropins is completely blocked with administration of Type-1 GnRH receptor antagonists, both in vitro and in vivo [65][66][67]. Likewise, similar blocking effects of Type-1 receptor antagonists were found on GnRH II-induced ovulation in female musk shrews (TABLE 2) [68].…”
Section: Role Of Mammalian Gnrh II In Gonadotropin Releasementioning
confidence: 68%
“…More recent evidence contradicts these earlier findings; in vitro studies using rat hemi-pituitaries found that GnRH II had no significant FSH-or LH-releasing ability, except at very high doses, and no selective releasing activity for FSH [73,74]. Likewise, in vivo studies in sheep and rhesus monkeys, as well as an in vitro investigation using cultured primate pituitaries, have reported no selective FSH-releasing activity for GnRH II [65][66][67]. Collectively, the data indicate that GnRH II has only weak actions as a selective FSH-RF, if at all.…”
Section: Role Of Mammalian Gnrh II In Gonadotropin Releasementioning
confidence: 88%
See 1 more Smart Citation
“…GnRH-II was found to induce expression of LH and FSH in sheep but not in the presence of antide, a specific GnRH-I receptor antagonist [60]. GnRH-II did little to augment the activity of GnRH-I on gonadotropin secretion.…”
Section: Updatementioning
confidence: 88%
“…Genes for a type II GnRH receptor (nomenclature of Ref. 13) have been identified in several mammals (14,16,18,19). Type II GnRH receptors have high affinity for GnRH II and much lower affinity for GnRH I (14,16).…”
mentioning
confidence: 99%